Korelasi Komunikasi Interpersonal Efektif & Kualitas Layanan Tim Medis terhadap Kepuasan Pasien - Oisina, Ilona Vicenovie; Osidhi, Ivonne Ruth Vitamaya (Jurnal Komunikasi Islam, 2018)
Effective medical staff-patient interpersonal communication is a central clinical function. This study was a survey of 96 patients at Claudia Bagan Batu Hospital, Riau attempting to contribute the role of interpersonal communication and a hospital's service quality towards patient satisfaction. By utilizing correlation analysis between variables and regression to each variable, this study has found a strong correlation between variable of interpersonal communication and variable patient satisfaction (0.805) and the moderate correlation between the variable of service quality and patient satisfaction (0.639). In short, it has revealed that there has been a strong influence between interpersonal communication and service quality at Claudia Bagan Batu Hospital on patient satisfaction (87.8%).